Mental health in adolescents displaced by the armed conflict: findings from the Colombian national mental health survey (2020)
Background: Colombia has one of the largest populations of internally displaced individuals by an armed confict. However, there is no data demonstrating its efect on health, particularly in adolescents. Purpose: To describe the prevalence and associations of mental illness in the adolescent population displaced by violence in Colombia. Methods: We conducted a secondary analysis of the 2015 National Mental Health Survey (NMHS), which provides data of mental health issues (SRQ), mental health disorders (CIDI-CAPI) and sociodemographic characteristics. Results: Of the 1754 adolescents interviewed 5.3% (95% CI 4.1 to 6.9) mentioned a change in residence due to violence. Among them 38.5% lived in poverty compared to 23.6% of those non-displaced by the confict. Suicidal thoughts and suicide attempt were present in 19.8% and 9.1% of displaced adolescents respectively, compared to 5.8% and 2.1% of non-displaced adolescents. The prevalence of post-traumatic stress disorder (PTSD) and any mental health disorder (measured with the CIDI-CAPI) was higher in the displaced population 12.3%, 11% respectively, in contrast to 2.1% and 7% of those non-displaced. Finally, anxiety and depressive disorders were more common among displaced adolescents. Conclusion: A higher prevalence of mental health conditions and disorders is observed among displaced adolescents.